PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pengguna Produk Skintific Kota Semarang) - Hendriyani, Mala; Wahyunigsih, Susanti; Yuliati, Yuliati (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
The purpose of this study is to determine the effect of brand image and product quality on customer loyalty through customer satisfaction as an intervening variable on skintific product users. To determine the effect of brand image, product quality, and customer satisfaction on customer loyalty. The independent variables in this study are brand image and product quality. The dependent variable in this study is Customer Loyalty. The intervening variable in this study is customer satisfaction. The research method used in this study is Path Analysis. The population of this study is users of skintific products in the city of Semarang. The sample in this study amounted to 114 people using non-probability sampling, namely research selecting samples intentionally and subjectively. The data collection method is by distributing questionnaires via Google Form. The types of data used are primary data and secondary data. The results of the study indicate that brand image has an effect on customer satisfaction with t count > t table 3.083 > 1.659 and significance 0.003 < α 0.05. And product quality has an effect on customer satisfaction with t count > t table 9.566 > 1.659 and significance 0.000 < α 0.05. Brand image does not have an effect on customer loyalty with t count < t table 0.433 < 1.659 and significance 0.666 > α 0.05, while product quality has an effect on customer loyalty with t count > t table 10.342 > 1.659 and significance 0.000 < α 0.05. Customer Satisfaction influences Customer Loyalty with t count > t table 2.106 > 1.659 and significance 0.038 > α 0.05.